2002
DOI: 10.1061/(asce)1076-0342(2002)8:1(2)
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Implementation of Infrastructure Priority Projects: Case Study in Palestine

Abstract: A strategy was developed for implementation and management of multisector urban infrastructure projects. The strategy includes risk-based analytical hierarchy process ͑AHP͒ for project prioritization that is based on project deliverables and project life-cycle and implementation guidelines. The expert-opinion elicitation process used for this study consists of a variation of the Delphi technique, scenario analysis, civil works, and nuclear industry recommendations. The AHP methodology utilizes a multicriteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…In this section, it is also important to compare SIIP and the models presented by Ziara et al (2002) and Lambert et al (2012), which are very important because they were the first to have been developed in this field, although there is some evidence showing that SIIP is different and an advanced model. The most important differences is that Ziara et al (2002) and Lambert et al (2012) were developed to prioritize investments in developing countries, and the SIIP has been developed to prioritize investments in developed countries, as it has been mentioned throughout the paper.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this section, it is also important to compare SIIP and the models presented by Ziara et al (2002) and Lambert et al (2012), which are very important because they were the first to have been developed in this field, although there is some evidence showing that SIIP is different and an advanced model. The most important differences is that Ziara et al (2002) and Lambert et al (2012) were developed to prioritize investments in developing countries, and the SIIP has been developed to prioritize investments in developed countries, as it has been mentioned throughout the paper.…”
Section: Discussionmentioning
confidence: 99%
“…There are two papers, Ziara et al (2002) and Lambert et al (2012), which have not been considered in that revision, but they are very interesting because they present an index to prioritize infrastructure. Although, they are used as theoretical references in this paper, both of them present some conceptual differences with SIIP.…”
Section: Decision-making In the Field Of Infrastructure Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, this research focused on the following research question: what are the barriers that infrastructure organizations face when establishing and implementing an asset management system and how do they vary between developing and developed economies? Poister et al 2013;Shiferaw et al 2002;FHWA 2007;Schraven et al 2011 Lack of identified processes and control procedures (e.g., no consideration for budgets scenarios; no criteria to optimize use of funds; undefined repairs' strategies) Mizusawa and McNeil 2006;McNeil et al 2000;Hassanain et al 2003;Halfawy, 2008;Arif and Bayraktar 2012 Inconsistent decisions by the decision makers (e.g., the organization decides to build a wastewater treatment plant without taking into account a project to connect the network's pipes) Grussing 2014;Shiferaw et al 2002;FHWA, 2007;Schraven et al 2011;Arif and Bayraktar 2012;Vanier 2001;Flyvbjerg 2007 Managerial/ Organizational: Lack of top management support (e.g., no action decisions are taken about any management system development; no long term support of management plans; no implementation of planned criteria) Brunetto et al 2014;Lizarralde et al 2013;Mizusawa and McNeil 2006;Cooksey et al 2011 Lack of communication channels within organizations and departments (e.g., different departments do not share their plans to create a general plan for the organization) FHWA 2007; Brunetto et al 2014;Cooksey et al 2011;Lizarralde et al 2013;Vanier 2001;Yankov and Kleiner 2001 Lack of scope and job description within the organization/ agency (e.g., there is no clear identification of the responsibilities and authorities for managers in different levels in the organization) Atkinson et al 2006;Arts and Van Lamoen 2005;Ziara et al 2002;PMI 2013 Lack of performance monitoring (e.g., no clear criteria; no announced indicators; unclear procedures) Cooksey et al 2011;…”
Section: Literature Review On Potential Asset Management Barriersmentioning
confidence: 99%